2021
DOI: 10.1108/bfj-05-2021-0522
|View full text |Cite
|
Sign up to set email alerts
|

Weight-loss diets among female Korean adolescents: a pilot study based on a social media platform

Abstract: Purpose The study aimed to analyse the nutritional quality of self-proposed or prescribed weight-loss diets shared by female Korean adolescents through a social media platform and identified potential dietary problems. Design/methodology/approach A total of 317 weight-loss diets, shared by 107 female adolescents between the ages of 12 and 18 in April 2019, were collected from three Kakao Open Chat rooms of which the main topic was “weight-loss diet”. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Занепокоєння зовнішнім виглядом надзвичайно поширене в підлітковому віці. Окрім реальних ризиків для здоров'я, пов'язаних із ожирінням і неправильним харчуванням, підлітки стикаються з ідеалом нереально худорлявої краси [16]. На жаль, цей надмірний акцент на важливості худорлявості сприймається молоддю як шлях до краси, успіху та здоров'я.…”
Section: результати дослідженняunclassified
“…Занепокоєння зовнішнім виглядом надзвичайно поширене в підлітковому віці. Окрім реальних ризиків для здоров'я, пов'язаних із ожирінням і неправильним харчуванням, підлітки стикаються з ідеалом нереально худорлявої краси [16]. На жаль, цей надмірний акцент на важливості худорлявості сприймається молоддю як шлях до краси, успіху та здоров'я.…”
Section: результати дослідженняunclassified
“…Previous research has shown that when social support is combined with weight-loss techniques in online settings, patients with obesity have better weight-loss outcomes as well as coping better emotionally with their condition (Hwang et al ., 2010; Yan, 2018). It is worth noting that digital environments need to be controlled as advocating the free sharing of self-imposed or prescribed diets on social media can promote unhealthy eating habits (Kim and Kim, 2022). Similarly, another component that positively influences obesity treatment is perceived self-efficacy, which is a belief in one's ability to take control over the self and external factors (Bandura, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For overweight and obese individuals, it is highly recommended to decrease their body weight through adopting lifestyle modification including lowering calories intake concomitant with increase physical activities [9]. However, many young people, especially females, with normal BMI misperceive their body weight due to dissatisfaction with body image in addition to psychological and socio-cultural factors [6,10,11]. Those people usually desire to be thinner by practicing unhealthy diet regimens that cause inappropriate weight reduction and nutritional disorders [12][13][14].…”
Section: Introductionmentioning
confidence: 99%